Amara and the bats - Reynolds, Emma (New York : Atheneum Books for Young Readers, 2021)
Amara loves bats, so when she learns there are none near her new home due to habitat loss, she overcomes her feelings of helplessness and inspires her community to take action. Includes facts about bats and bat houses.
Ages 4-8.
Grades 2-3.
Keywords: Environmentalism -- Juvenile fiction; Bats -- Juvenile fiction; Habitat (Ecology) -- Juvenile fiction; Animal rights activists -- Juvenile fiction; Moving, Household -- Juvenile fiction; Picture books